Poultry litter and cow dung biochar as P sources for cowpea cultivation in two Ghanaian soils - Nartey, Eric K.; Sulemana, Nasirudeen; Razak, Awudu; Adjadeh, Thomas A.; Akumah, Asiwome M.; Amoatey, Christiana; Abekoe, Mark K. (Frontiers in Agronomy, 2023)
Introduction The main constraint to cowpea, Vigna unguiculata, production in West Africa is unavailability of applied phosphorus due to ligand exchange with clay minerals and precipitation reactions facilitated by low pH and low organic matter. Materials and methods To overcome this challenge, cow dung biochar (CB) and poultry litter biochar (PB) were applied as P sources for cowpea cultivation in Plinthustult and Kandiustalf soil in Ghana. The biochar types and triple super phosphate (TSP) were applied to meet the standard phosphorus requirement (SPR) and ½ SPR of the soils. Basal K from KCl was added to the TSP treatment. In addition to a non-amended soil, the treatments were triplicated and arranged in a completely randomized design in a screen house for an efficacy trial using cowpea as the test crop. Moisture content was maintained at 80% field capacity. Results and discussion Hundred cowpea seed weight was 20.3 g and 19.6 g for the TSP-amended Plinthustult at SPR and ½ SPR, respectively. This increased to 25.1 g and approximately 27 g at SPR and ½ SPR in the CB- and PB-amended Plinthustult, respectively. Hundred seed weight for TSP at both rates was similar in the two soils. The PB-amended Kandiustalf at SPR had seed with a weight of 27.02 g, 1.1 g heavier than the ½ SPR. The CB-amended Kandiustalf at both rates had 100 seeds weighing 25 g. Residual available P was 334.2 mg/kg and 213.2 mg/kg at SPR and ½ SPR, respectively, in the Plinthustult as opposed to a paltry 2.5 mg/kg at SPR in the TSP counterpart. The study recommends for the two biochar types to be applied at ½ SPR.